Cluster formation in oxygen-deficient La0.5Yb0.5Ba2Cu3Oy - Guskos, N.; V. Likodimos; Typek, J.; Wabia, M.; Fuks, H. (Radiation Effects and Defects in Solids, 1999)
The EPR spectra of the oxygen-deficient La0.5Yb0.5Ba2Cu3Oy mixed phase has been investigated as a function of temperature. At low temperatures (T<15 K), an intense EPR line indicating the presence of magnetic clusters associated with spin-polarized clusters of copper ions through delocalized oxygen holes, has been detected. Both the EPR linewidth and g-factor of the latter EPR spectrum exhibit strong temperature dependence indicative of short-range order effects. At higher temperatures (T>30 K), the EPR spectrum reveal the contribution of Cu2+ defects and a broad EPR spectrum due to Yb3+ ions which is compared with the corresponding one in Y0.5Yb0.5Ba2Cu3Oy compounds.
cited By 0